Answer:
x= -10/3
y= -8/9
Step-by-step explanation:
2x+1=3(y−1);6(2y−1)=5x
Rewrite equations:
2x+1=3y−3;12y−6=5x
Step: Solve2x+1=3y−3for x:
2x+1=3y−3
2x+1+−1=3y−3+−1(Add -1 to both sides)
2x=3y−4
2x2=3y−42(Divide both sides by 2)
x=32y−2
Step: Substitute32y−2forxin12y−6=5x:
12y−6=5x
12y−6=5(32y−2)
12y−6=152y−10(Simplify both sides of the equation)
12y−6+−152y=152y−10+−152y(Add (-15)/2y to both sides)
92y−6=−10
92y−6+6=−10+6(Add 6 to both sides)
92y=−4
92y92=−492(Divide both sides by 9/2)
y=−89
Step: Substitute−89foryinx=32y−2:
x=32y−2
x=32(−89)−2
x=−103(Simplify both sides of the equation)